Female entrepreneurs owning small businesses in the agriculture sector in Comoros, Africa: challenges faced in the conventional system - Bacha, Asmaou Mohamed; Zakariyah, Habeebullah; Mohd Yusoff, Syarah Syahira; Hassan, Rusni (Penerbit Universiti Sains Islam Malaysia, 2025)
The purpose of this research is to identify the challenges faced by female entrepreneurs in the agriculture sector owning small business in the conventional system in Comoros. To achieve this objective, data was collected using a qualitative research method. With that, structured interviews were conducted between the researcher and female entrepreneurs owning small businesses in the agriculture sector in Comoros. The results suggest that, owning a small business, collateral, conditions attached to the loans and interest rate are the main challenges that entrepreneurs are facing in the conventional system in Comoros. These challenges slow down the growth of female entrepreneurs in the agriculture sector in Comoros and limit their contribution to local production and household income. This re-enforce the need for more suitable financial solutions by national stakeholders, particularly financial institutions and government agencies in the country to support female entrepreneurs and strengthen the agricultural sector.